The Effect of Flavonoids from Mahkota Dewa Fruit Extract (Phaleria macrocarpa) on Inflammation Factors (IL-1β and IL-6) and Estrogen Receptor Alpha (ERα) in The Ovaries of Endometriosis Model Mice - Destikatari, Lovin; Rahajeng; Baihaqi, Irfani (Asian Journal of Health Research, 2025)
Introduction: Endometriosis is a gynecological disorder characterized by the growth of endometrial tissue outside the uterus. The disease is marked by uncontrolled cell proliferation, increased cell aggressiveness, apoptosis defects, and an inflammatory microenvironment. Phaleria macrocarpaa, a native Indonesian plant, contains flavonoids that function as antioxidants and have anti-inflammatory and antimicrobial properties. Previous research has shown that flavonoids from Phaleria macrocarpa can inhibit endometriosis lesion growth by regulating cell apoptosis. Material and Methods: This study is an experimental study using a randomized post-test-only control group design. Six groups were included: a negative control, a positive control, and four treatment groups receiving Phaleria macrocarpa flavonoid extract at concentrations of 3.75%, 7.5%, 11.25%, and 15%. The primary data obtained were then examined using SPSS 26.0. Results: IL-1β, IL-6, and ERα levels in the treatment groups were lower than in the positive control group, with significant differences between each group. Higher extract doses were associated with a greater reduction in inflammatory mediators. Regression analysis demonstrated a strong correlation between Phaleria macrocarpa extract administration and decreased levels of IL-1β (86%), IL-6 (94%), and ERα (95%). Conclusion: In endometriosis model mice, administering Phaleria macrocarpa fruit extract can lower the concentration of IL-1β, IL-6, and ERα. There is a correlation between the reduction of concentration of IL-1β, IL-6, and ERα in endometriosis model mice and various doses of Phaleria macrocarpa fruit extract.